Analysis Of QRIS Usage Among Generation Z In Banda aceh - Adnan, Muhammad; Akmal Riza; Nisa Andaiyani (IAIN Langsa, 2024)
The QRIS product issued by Bank Indonesia is one of the conveniences in digital transactions in society, this study aims to analyze the influence of knowledge and social media on Generation Z's interest in using QRIS in Banda Aceh City. The quantitative research approach methodology is associative, with primary data collection through questionnaires distributed to 100 respondents using simple random sampling techniques. Data analysis was carried out using multiple linear regression to test the influence or relationship between variables. The results of the study show that knowledge and social media have a positive and significant effect on Generation Z's interest in using QRIS. Specifically, knowledge has an influence of 79.10% on the interest in using QRIS, while social media contributes 38.50%. The results of the study provide an important contribution to the development of digital marketing strategies in increasing QRIS adoption, especially among Generation Z. The recommendation of this research is for the government, business actors, and digital payment service providers to increase educational and promotional campaigns through social media to increase awareness and use of QRIS in the community.